Temperature cycling improves in vivo recovery of cold‐stored human platelets in a mouse model of transfusion. Issue 6 (24th September 2012) - Xu, Fei; Gelderman, Monique P.; Farrell, John; Vostal, Jaroslav G.
<x xml:space="preserve">Abstract</x> BACKGROUND: Platelet (PLT) storage at room temperature (RT) is limited to 5 days to prevent growth of bacteria, if present, to high levels. Storage in cold temperatures would reduce bacterial proliferation, but cold‐exposed PLTs are rapidly cleared from circulation by the hepatic Ashwell‐Morell (AM) receptor, which recognizes PLT surface carbohydrates terminated by β‐galactose. We cycled storage temperature between 4 and 37°C to preserve PLT function and reduce bacterial growth. STUDY DESIGN AND METHODS: Temperature‐cycled (TC) human PLTs were stored at 4°C for 12 hours and then incubated at 37°C for 30 minutes before returning back to cold storage. PLTs stored at RT or at 4°C (COLD) or TC for 2, 5, and 7 days were infused into SCID mice and the in vivo recovery was determined at 5, 20, and 60 minutes after transfusion. RESULTS: PLTs stored for 2 days in COLD had significantly lower in vivo recoveries than RT PLTs. TC PLTs had improved recoveries over COLD and comparable to RT PLTs. After 5‐ and 7‐day storage, TC PLTs had better recoveries than RT and COLD PLTs. PLT surface β‐galactose was increased significantly for both COLD and TC PLTs compared to RT. Blocking of the AM receptor by asialofetuin increased COLD but not TC PLT recovery. CONCLUSION: TC cold storage may be an effective method to store PLTs without loss of in vivo recovery. The increased β‐galactose exposure in TC PLTs suggests that mechanisms in addition to AM receptors may mediate clearance of cold‐stored PLTs.